Business Model Canvas: Nobrella / Intan Najihah Mohamad Napiah - Mohamad Napiah, Intan Najihah (2020)
Nobrella product was introduced by Lolly Brully Enterprise. Nobrella is a handless umbrella, a new Lily’s product that used a few combinations of famous technologies that can help pedestrians to use it in a comfortable and convenient way. We believe that they will be amazed and interested in our product. Handless Umbrella is a new kind of umbrella that is developed without hand stick. This product can help it users to use it with ease. Besides, the price of this product is more affordable that other existing product and can be used for a longer period since it is provided with high quality material in order to help customer to protect themselves when going outdoors. This product also works in convenient ways. This product is a hands-free umbrella where it helps users to use the umbrella without having to hold them. The product also has a shoulder strap that supports the users’ posture. An overall product is make from high quality plastic that protects the users from UV rays. It has button as the side of the umbrella that able to open or close the aerodynamic shape of protector. The users do not have problem when using the product around crowded place since the product would not be a nuisance. Besides, the product easy to be keep at a closed space